IMPLEMENTATION OF WEB GOVERNMENT AS MEDIA INFORMATION POTENTIAL VILLAGE SUKARAJA - Dedi Irawan; Ricky Wijaya (IJISCS (International Journal of Information System and Computer Science), 2017)
The development of information technology is so rapid that one of them in the form of the Internet. E-government In village Sukaraja is one of the most exciting sites in Sukaraja, the village of Sukaraja, the governance structure of the village of Sukaraja and all related information in the village of Sukaraja. System development Life Cycle (SDLC) approach includes planning stages, analysis, in and system implementation, tools in system development process using DAD (Data Flow Diagram), DFD (Data Flow Diagram), and flowchart. In the making of this website use HTML programming language (Hypertext Markup Language), PHP (Hypertext Preprocessor), CSS (Cascading Style Sheet), JQUERY, Java script and presentation of data in the form of MySQL. With the existence of E-government In the Village Sukaraja aims to provide benefits for the wider community about obtaining Village information in a way easily, quickly, effectively and efficiently without knowing the deadline anytime and anywhere.